Improving the quality of organic fertilizer by utilizing local microorganisms (LMO) of cassava tapai - Zainuddin, Dian Utami; Alim, Nurmaranti; Ramadan, Laode Muh Asdiq Hamsin; Ardiana, Ardiana (Anjoro: International Journal of Agriculture and Business, 2024)
Local Micro Organism Solution (LMO Solution) is a fermentation solution made from various locally available resources, both plants and animals. The LMO solution contains micro and macronutrients and bacteria that have the potential to decompose organic matter in the soil, stimulate plant growth, and act as a pest and plant disease control agent. It is easy to obtain and makes it possible to increase farmers’ desire to process agricultural waste. This research aims to determine the quality of organic fertilizer from livestock manure by utilizing local microorganisms (LMO) in cassava. This research was carried out from March 2023 to December 2023. The research was carried out at the Soil Laboratory of Hasanuddin University and the Greenhouse of the Faculty of Agriculture and Forestry, West Sulawesi University. The experimental design used in this planting test was a Completely Randomized Design (CRD), consisting of four LMO dose treatments, with each treatment carried out three times. The results of the research showed that the planting media provided by LMO tapai cassava had a significant effect on increasing the availability of the nutrients Nitrogen (N) and Phosphorus (P). The treatment regimen involving a dose of 240 ml (M3) showed the highest average values ​​for nutrient content, specifically 0.25% for Nitrogen (N) and 13.75 ppm for Phosphorus (P2O5). Providing cassava tapai LMO in the planting medium had a significant effect on the average height of spinach plants at the observation time of 10 day after planting (DAT) and the average leaf weight. The M3 treatment showed the highest average value of plant height at 10 DAT of 7.17 cm and leaf weight of 0.73 g.